The Qur'ānic recitation traditions of the Tatars and Bashkirs in Russia: Evolution of style. (1st December 2017) - Imamutdinova, Zilia
This article for the first time discusses the evolution of the Russian Turkic (Tatar and Bashkir) Qur'ānic recitation tradition as an integral phenomenon and, in parallel, identifies the differences in these two ethno-regional forms, provides the historical context to enable an understanding of the nature of changes, describes its development stages and outlines the specifics of professional and non-professional forms of the Qur'ānic recitation by Tatars and Bashkirs in terms of ethnical background and relations with the classical Arabic tradition. It summarizes the unique facts found in historical and other scientific sources, field research materials (interviews, audio and video records) and the results of the author's scientific research for more than 25 years. Music notation and computer graphs are used for illustrative purposes.